Whole‐brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction. Issue 1 (26th February 2021) - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Doerfler, Arnd; Uder, Michael; Zaiss, Moritz; et al.
Abstract : Purpose: To enable whole‐brain quantitative CEST MRI at ultra‐high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online‐customized (FOCUS) parallel transmission (pTx) excitation pulses and B 1 + correction to achieve homogenous whole‐brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good B 1 + correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using B 1 + correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter‐subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single‐point B 1 + correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single‐point B 1 + correction can be used to achieve quantitative CEST measurements at ultra‐high magnetic field strengths. Compared to previous B 1 + correction methods, acquisition time can be reduced as additional scans required for B 1 + correction can be omitted.